A prospective study of comparing waist circumference and BMI as predictors for the kidney damage progression - Jou-Yin Chen; Yukiko Wagatsuma (PLoS ONE, 2025)
Objective Chronic kidney disease (CKD) is irreversible and linked with various adverse health outcomes and diminished quality of life. Although obesity is recognized as a risk factor for the progression of kidney damage, reliance solely on body mass index (BMI) to measure obesity has been increasingly questioned. The use of other indicators that reflect more on abdominal adiposity like waist circumference (WC) have been proposed. This study aims to determine whether WC can serve as an alternative predictor of kidney damage progression. Methods This prospective study enrolled individuals with normal kidney function during their annual health checkups from April 2016 to March 2019. Data on BMI, WC, WC-related devices, health-related lifestyle, and comorbidities were collected at baseline. WC was categorized using various definitions and analyzed for its association with the risk of kidney damage progression, taking into account BMI categories. The participants were monitored until March 2023 to observe kidney damage progression. Results Out of the 4,129 participants, WC showed a higher risk of kidney damage progression in males (HR=1.01–1.39, p-value<0.05). These associations were not observed in females. After adjusting for BMI categories, the associations disappeared. Males in the overweight BMI category, defined as a BMI ≥ 25 kg/m2, showed a significantly increased risk of kidney damage progression (HR = 1.69, p-value < 0.0001). Conclusions The findings indicate that waist circumference significantly affects the progression of kidney damage in males. However, the study also reaffirms BMI as a dependable predictor of kidney damage. It underscores the importance of maintaining normal ranges for both BMI and waist circumference to reduce the risk of progressing kidney damage.